Computational Fluid Dynamics in Torque Converters: Validation and Application - Jean Schweitzer; Jeya Gandham (International Journal of Rotating Machinery)
This article describes some of the computational fluid dynamics (CFD) work being done on three-element torque converters using a commercially available package CFX TASCflow. The article details some of the work done to validate CFD results and gives examples of ways in which CFD is used in the torque-converter design process. Based on the validation study, it is shown that CFD can be used as a design and analysis tool to make decisions about design direction. Use of CFD in torque converters is a developing field. Thus, more work needs to be done before the requirement of hardware to validate designs can be fully eliminated. This article demonstrates the confidence level in torque converter CFD and demonstrates how it can be used to assist torqueconverter design today.